\(\frac{2020}{2019}-\frac{2018}{2017}+\frac{2}{2017\cdot2019}3\cdot x-18\)
\(\frac{x+4}{2017}+\frac{x+3}{2018}+\frac{x+2}{2019}+\frac{x+1}{2020}\)
Tìm x biết \(\frac{x-1}{2017}+\frac{x-2}{2018}-\frac{x-3}{2019}=\frac{x-4}{2020}\)
Ta có : \(\frac{x-1}{2017}+\frac{x-2}{2018}-\frac{x-3}{2019}=\frac{x-4}{2020}\)
\(\Rightarrow\frac{x-1}{2017}+\frac{x-2}{2018}=\frac{x-4}{2020}+\frac{x-3}{2019}\)
\(\Rightarrow1+\frac{x-1}{2017}+1+\frac{x-2}{2018}=1+\frac{x-4}{2020}+1+\frac{x-3}{2019}\)
\(\Rightarrow\frac{2016+x}{2017}+\frac{2016+x}{2018}=\frac{2016+x}{2020}+\frac{2016+x}{2019}\)
\(\Rightarrow\frac{2016+x}{2017}+\frac{2016+x}{2018}-\frac{2016+x}{2019}-\frac{2016+x}{2020}=0\)
\(\Rightarrow\left(2016+x\right)\left(\frac{1}{2017}+\frac{1}{2018}-\frac{1}{2019}-\frac{1}{2020}\right)=0\)
\(\text{Mà :
}\)\(\frac{1}{2017}+\frac{1}{2018}-\frac{1}{2019}-\frac{1}{2020}\ne0\)
\(\text{Nên : }\) \(2016+x=0\)
\(\Rightarrow x=-2016\)
Ta có : x−12017 +x−22018 −x−32019 =x−42020
⇒x−12017 +x−22018 =x−42020 +x−32019
⇒1+x−12017 +1+x−22018 =1+x−42020 +1+x−32019
⇒2016+x2017 +2016+x2018 =2016+x2020 +2016+x2019
⇒2016+x2017 +2016+x2018 −2016+x2019 −2016+x2020 =0
⇒(2016+x)(12017 +12018 −12019 −12020 )=0
Mà : 12017 +12018 −12019 −12020 ≠0
Nên : 2016+x=0
⇒x=−2016
Giải phương trình
\(\frac{x-2}{2017}+\frac{x-3}{2018}=\frac{x-4}{2019}+\frac{x-5}{2020}\)
Ta có:\(\frac{x-2}{2017}+1+\frac{x-3}{2018}+1=\frac{x-4}{2019}+1+\frac{x-5}{2020}+1\)
\(\Rightarrow\frac{x+2015}{2017}+\frac{x+2015}{2018}-\frac{x+2015}{2019}-\frac{x+2015}{2020}=0\)
\(\Rightarrow\left(x+2015\right)\left(\frac{1}{2017}+\frac{1}{2018}-\frac{1}{2019}-\frac{1}{2020}\right)=0\)
Mà \(\frac{1}{2017}+\frac{1}{2018}-\frac{1}{2019}-\frac{1}{2020}>0\)
\(\Rightarrow x+2015=0\Rightarrow x=-2015\)
\(S=\left\{-2015\right\}\)
gợi ý
2017-x-2=2018-3-x=2019-4-x=2020-5-x
\(\frac{x-2}{2017}+\frac{x-3}{2018}=\frac{x-4}{2019}+\frac{x-5}{2020}\)
\(\Leftrightarrow\left(\frac{x-2}{2017}+1\right)+\left(\frac{x-3}{2018}+1\right)=\left(\frac{x-4}{2019}+1\right)+\left(\frac{x-5}{2020}+1\right)\)
\(\Leftrightarrow\frac{x-2+2017}{2017}+\frac{x-3+2018}{2018}=\frac{x-4+2019}{2019}+\frac{x-5+2020}{2020}\)
\(\Leftrightarrow\frac{x+2015}{2017}+\frac{x+2015}{2018}-\frac{x+2015}{2019}-\frac{x+2015}{2020}=0\)
\(\Leftrightarrow\left(x+2015\right)\left(\frac{1}{2017}+\frac{1}{2018}-\frac{1}{2019}-\frac{1}{2020}\right)=0\)
\(\Leftrightarrow x+2015=0\)
\(\Leftrightarrow x=-2015\)
So sánh phân số sau:
\(\frac{2017\cdot2018}{2017\cdot2018+1}\)và\(\frac{2018\cdot2019}{2018\cdot2019+1}\)
Ta đi so sánh \(\frac{2017.2018+1}{2017.2018}\)với\(\frac{2018.2019+1}{2018.2019}\)có :
\(\frac{2017.2018+1}{2017.2018}=\frac{2017.2018}{2017.2018}+\frac{1}{2017.2018}=1+\frac{1}{2017.2018}\left(\cdot\right)\)
\(\frac{2018.2019+1}{2018.2019}=\frac{2018.2019}{2018.2019}+\frac{1}{2018.2019}\left(\cdot\cdot\right)\)
\(\frac{1}{2017.2018}>\frac{1}{2018.2019}\left(\cdot\cdot\cdot\right)\)Từ \(\left(\cdot\right);\left(\cdot\cdot\right)\&\left(\cdot\cdot\cdot\right)\Rightarrow\frac{2017.2018+1}{2017.2018}>\frac{2018.2019+1}{2018.2019}\)
\(\Leftrightarrow\frac{2017.2018}{2017.2018+1}< \frac{2018.2019}{2018.2019+1}.\)
#)Trả lời :
\(\frac{2017\times2018}{2017\times2018+1}=\frac{0}{1}=0\)
\(\frac{2018\times2019}{2018\times2019+1}=\frac{0}{1}=0\)
\(\Rightarrow\frac{2017\times2018}{2017\times2018+1}=\frac{2018\times2019}{2018\times2019+1}\)
Tìm x
\(\frac{x-2017}{2015.2016}+\frac{x-2018}{2016.2017}+\frac{x-2019}{2017.2018}+\frac{x-2020}{2018.1019}=\frac{1}{2015}+\frac{1}{2016}+\frac{1}{2017}+\frac{1}{1018}\)
1,So sánh A và B
\(A=\frac{2017\cdot2018-1}{2017\cdot2018}\)
\(B=\frac{2018\cdot2019-1}{2018\cdot2019}\)
\(A=\frac{2017.2018-1}{2017.2018}=1-\frac{1}{2017.2018}\)
\(B=\frac{2018.2019-1}{2018.2019}=1-\frac{1}{2018.2019}\)
Có \(\frac{1}{2017.2018}>\frac{1}{2018.2019}\)
\(\Rightarrow A< B\)
\(A=\frac{2017.2018-1}{2017.2018}=1-\frac{1}{2017.2018}\)
\(B=\frac{2018.2019-1}{2018.2019}=1-\frac{1}{2018.2019}\)
Do \(\frac{1}{2017.2018}>\frac{1}{2018.2019}\)nên \(1-\frac{1}{2017.2018}< 1-\frac{1}{2018.2019}\)
Vậy \(A< B\)
tính nhanh
\(\frac{19}{37}+\left(1-\frac{19}{37}\right)\)
\(\frac{7}{13}\cdot\frac{5}{14}\cdot\frac{39}{15}\)
\(2\frac{3}{7}\cdot\frac{1}{2}-\frac{1}{2}\cdot\frac{3}{7}+\frac{1}{3}\)
\(\frac{9}{5}:\frac{17}{15}+\frac{8}{5}:\frac{17}{15}\)
\(\frac{2017}{2018}\cdot\frac{1}{2019}+\frac{2017}{2018}:\frac{2019}{2018}+\frac{1}{2018}\)
\(\frac{637\cdot527-189}{526\cdot637+448}\)
\(\frac{4}{5\cdot7}+\frac{4}{7\cdot9}+\frac{4}{9\cdot11}+...+\frac{4}{23\cdot25}\)
dấu . là dấu nhân nha mọi người
\(\frac{19}{37}+\left(1-\frac{19}{37}\right)\)
\(=\frac{19}{37}+1-\frac{19}{37}\)
\(=\left(\frac{19}{37}-\frac{19}{37}\right)+1\)
\(=0+1=1\)
\(\left(1+\frac{1}{2}+\frac{1}{3}+...+\frac{1}{2017}\right).x+2017=\frac{2018}{1}+\frac{2018}{2}+\frac{2020}{3}\). Tìm x
Cho x, y, z thỏa mãn:
\(\frac{x}{2017}+\frac{y}{2018}+\frac{z}{2019}=1\)
\(\frac{2017}{x}+\frac{2018}{y}+\frac{2019}{z}=0\)
CMR:\(\frac{x^2}{2017^2}+\frac{y^2}{2018^2}+\frac{z^2}{2019^2}=1\)